What Do Medical Students Learn from an OSCE? An Exploratory Study in Indonesia - Nurul Qanitah Shahabuddin; Andi Alfian Zainuddin; Ichlas Nanang Afandi; Irwin Aras; Bau Dilam Ardyansyah; Muh. Idham Rahman (Education in Medicine Journal, 2026)
The Objective Structured Clinical Examination (OSCE) is a widely used assessment tool in medical schools, increasingly recognised for its impact on learning behaviour. This qualitative study explored the impact of OSCE on medical students’ learning behaviours at Alkhairaat University in Palu, Indonesia. Data were collected through six focus group discussions with 35 students purposively selected to represent diverse OSCE performances, and were analysed using thematic analysis. The results indicated that students perceived the OSCE as encouraging deeper learning, enhancing structured preparation, fostering skills relevant to professional growth, and reinforcing collaborative and self-regulated learning. Students also reported acquiring altruistic values through peer teaching and community-oriented behaviour. However, some students reported surface learning and dependency on rote memorisation. These findings highlight OSCE’s learning impact on medical students towards the accomplishment of not only clinical competence but also holistic professional development.